Enhancement in optoelectronic properties of lanthanum co-doped CdO: Zn thin films for TCO applications. (February 2022) - Sarath babu, R.; Narasimha murthy, Y.; Vinoth, S.; Isaac, R.S. Rimal; Mohanraj, P.; Ganesh, V.; Algarni, H.; AlFaify, S.
Abstract: This work reports on structural, electrical, optical, and photosensing properties of La and Zn co-doped CdO thin films. The co-doped CdO thin films were prepared on glass substrates using the nebulizer spray method at 350 °C. From the structural analysis, a decrease in the crystallite size from 20 to 16 nm is observed against the incorporation of La in CdO:Zn. Inclusion of La in CdO:Zn has also changed the surface morphology with a reduction in the roughness of the thin film samples. EDX analysis confirmed the incorporation of La with CdO: Zn in the prepared films. The bandgap value of the prepared samples increased with the increase in La concentration. A 1.5 wt% of La co-doped with CdO:Zn thin film sample produces low resistivity of 6.81 × 10 -4 Ω cm and a better figure of merit of 8.4 × 10 −4 Ω -1 . Finally, the fabricated photodetector with 1.5 wt% of La co-doped with CdO:Zn thin film shows a higher photocurrent and an ideality factor value of 3.4 . The photosensing properties of the fabricated (p-Si/CdO–Zn–La (1.5%)) photodetector shows a higher responsivity (R) value of 1.18 AW -1, specific detectivity (D*) value of 4.90 × 10 9 Jones, and external quantum efficiency (EQE) value of 274% with 3.0 mW/cm 2 light intensity. The switching characteristics of the photodetector show a faster rise time (2.9s) and fall time (3.6s) suggesting the fabricated device suitable for photosensing applications. Highlights: Doping of La in CdO:Zn has changed the surface morphology with a reduction in the roughness of the samples. A 1.5 wt% of La co-doped CdO:Zn sample produces low resistivity of 0.68 Ωcm and a better figure of merit of 8.4 × 10 −4 Ω -1 . Fabricated p-Si/CdO–Zn–La (1.5%)) photodetector shows a higher responsivity (R) value of 1.18 AW -1, specific detectivity (D*) value of 4.90 × 10 9 Jones, and external quantum efficiency (EQE) value of 274%. The switching characteristics of the photodetector show a faster rise time (2.9s) and fall time (3.6s).